Participatory Leadership of the School Principal in Developing the Quality of Education Services at State Senior High School 1 Menyuke - Paulus, Paulus; Zakso, Amrazi; Rustiyarso, Rustiyarso (Universitas Tanjungpura, 2024)
This research is motivated by the importance of providing quality educational services to the community, especially students and their parents. Through this research, it is hoped that clarity will be obtained regarding the influence of participative leadership on the quality of educational services at Menyuke 1 State High School. The problem is how does the principal implement participatory leadership, what is the quality of educational services, and how does the principal's participative leadership influence the quality of educational services at SMAN 1 Menyuke? This form of research is quantitative research with ex-post facto methods (measurements after the event) used to answer the research problem being studied. The units of analysis used in this research are teachers and staff. The minimum sample was determined using the Krecjie and Morgan Table, with a population of 42 teachers and school staff, a sample of 38 people was obtained. To collect data, a questionnaire was used which was given to teachers and school staff who were the research samples. Data analysis was carried out, descriptive statistics also used regression analysis and MANOVA. The results of the research show that the quality of educational services is classified as good, while the participative leadership of the principal of SMA Negeri 1 Menyuke is classified as high, and also specifically. The results of the study also show that there is a significant effect of the participative leadership of the principal on the quality of educational services at SMA Negeri 1 Menyuke.